Honeybee Pollen From Southern Chile: Phenolic Profile, Antioxidant Capacity, Bioaccessibility, and Inhibition of DNA Damage - Bridi, Raquel; Echeverría, Javier; Larena, Arturo; Nuñez Pizarro, Paula; Atala, Elias; De Camargo, Adriano Costa; Oh, Won Young; Shahidi, Fereidoon; Garcia, Olga; Ah-Hen, Kong S.; Montenegro, Gloria (Frontiers in Pharmacology, 2022)
Honeybee pollen (HBP) chemical composition is highly variable conforming to the floral and geographical origin of the pollen grains. The beneficial effects and functional properties of the HBP are well-known and have been mainly attributed to their high content of antioxidant polyphenols. In this work, twelve HBPs samples from the southwest region of Chile (X Región de Los Lagos) were characterized for the first time according to their botanical origin, phenolic composition, and antioxidant activity. The in vitro gastrointestinal digestion assay was done to simulate the human upper digestive tract. Selected honeybee pollen extracts (HBPEs) were assessed as bioaccessible fractions during an in vitro gastrointestinal digestion. Contents of phenolic compounds, antioxidant capacity, and recovery index of quercetin, myricetin, and cinnamic acid were monitored in different steps of gastrointestinal digestion. Furthermore, the protective effect of in vitro digested HBP towards DNA damage induced by peroxyl radicals was evaluated. The introduced species Brassica rapa L. (Brassicaceae), Lotus pedunculatus Cav. (Fabaceae), and Ulex europaeus L. (Fabaceae) predominated in all the HBPs analyzed, while the native species Buddleja globosa Hope (Scrophulariaceae), Luma apiculata (DC.) Burret (Myrtaceae), Embothrium coccineum J.R. Forst. & G. Forst. (Proteaceae) and Eucryphia cordifolia Cav. (Cunoniaceae) appeared less frequently. The content of polyphenols and antioxidant capacity in HBPEs achieved full bioaccessibility at the end of the intestinal digestion step. However, results obtained by a state-of-the-art technique (i.e. HPLC-DAD) demonstrated relatively low values of bioaccessible quercetin and cinnamic acid after the digestion process. In contrast, myricetin showed a high bioaccessibility in the intestinal digestion steps. The protective effect of in vitro digested HBP towards DNA damage induced by peroxyl radicals showed promising results (up to 91.2 % protection). In conclusion, HBPs from the X Region de Los Lagos are rich sources of phenolic antioxidants that protect DNA from strand breakage. Therefore, the potential of HBPEs in preventing gastric and/or intestinal cancer should be further considered.